Spectrophotometric Methods for Estimation of Ibuprofen and Pseudoephedrine Hydrochloride in Combined Dosage Form - Singhvi, I.; Chaturvedi, S.C. (Asian Journal of Chemistry, 2010)
Two accurate, economical and reproducible methods for estimation ofibuprofen and pseudoephedrine hydrochloride in combined dosage formhave been developed. The first method involves two-wavelength calculation.The two wavelengths selected for estimation of ibuprofen are 264.0nm and 254.5 nm while those for pseudoephedrine hydrochloride are 257.5nm and 266.5 nm. The second method is based on quantitative formationof hexane extractable copper(II) complex of ibuprofen which shows maximumabsorbance at 697 nm and benzene : carbon disulphide (3:1)extractable copper(II) complex of pseudoephedrine hydrochloride whichshows maximum absorbance at 437 nm. Both drugs obey Beer's law in the concentration ranges employed for these methods. Results of analysis were validated statistically.